In Vivo Evaluation of Miconazole-Nitrate-Loaded Transethosomal Gel Using a Rat Model Infected with Candida albicans - Zara Asghar; Talha Jamshaid; Usama Jamshaid; Asadullah Madni; Naheed Akhtar; Manar O. Lashkar; Heba A. Gad (MDPI AG, 2024)
Miconazole nitrate (MCNR), an antifungal drug, is used to treat superficial infections. The objective of the current study was to assess the antifungal effectiveness of MCNR-loaded transethosomal gel (MNTG) against Candida albicans in an in vivo rat model. The outcomes were compared with those of the miconazole nitrate gel (MNG) and marketed Daktarin® cream (2%) based on histopathological and hematological studies. The results of the skin irritation test revealed the safety profile of the MNTG. The MNTG demonstrated the greatest antifungal activity in the histological analysis and the visible restoration of the skin, and the rats revealed an apparent evidence of recovery. Compared to the untreated group, the treated group's lymphocyte and white blood cells counts increased, but their eosinophil counts decreased. In conclusion, MNTG exhibited the greatest antifungal activity, which might be connected to the improved skin permeability of the transethosome's nanosized vesicles. Therefore, it could be considered a promising carrier for topical usage and the treatment of cutaneous candidiasis. More clinical research needs to be performed in order to demonstrate its effectiveness and safe usage in humans.